Efforts to Improve Backhand Short Service Skills in Badminton Learning through the Peer Teaching Learning Model - Kosasih, Aldananda Diyanti; Lengkana, Anggi Setia; Rukmana, Anin (Universitas Majalengka, 2024)
This research aims to improve students' backhand short-serve skills in badminton learning through a peer teaching-learning model. The subjects in this research were class IV students at SDN Bongkok, consisting of 11 female students and 15 male students. The research method uses classroom action research (PTK) with a quantitative, qualitative approach, with a Kemmis and Mc Taggart model research design that focuses on reflection and continuous action cycles. Each cycle consists of planning, implementation, observation, and reflection. This data analysis was carried out qualitatively and quantitatively. Based on the data analysis, the learning outcomes were that in cycle 1, 50% or 13 students were declared complete; in cycle 2, 76.92% or 20 students were completed; and in cycle 3, 100% were declared complete. For student activity in cycle 1, it was 72.11, increasing in cycle 2 to 80.12, and in cycle 3, it reached 90.70. The IPKG 1 and IPKG 2 assessments also increase each cycle; in cycle 1, the IPKG 1 is 69%, IPKG 2 70%; in the second cycle, IPKG 1 is 77%, IPKG 2 is 80% and increases at the end of cycle 3, namely IPKG 1 98.8 IPKG 2 100 %. In conclusion, the application of the peer teaching-learning model in badminton learning can improve students' learning outcomes for backhand short-serve skills.